KONFLIK SOSIAL DALAM NOVEL LONCENG CINTA DI SEKOLAH GURU KARYA KHAIRUL JASMI - Fitri Kurnia Wati; Yasnur Asri; Muhammad Ismail Nasution (Faculty of Languages and Arts, Universitas Negeri Padang, 2013)
The purpose of this study are for describing (1) Individual social conflict that with his self in novel Lonceng Cinta di Sekolah Guru by Khairul Jasmi, (2) Individual social conflict with his family in novel Lonceng Cinta di Sekolah Guru by Khairul Jasmi, and (3) Individual social conflict with social environment in novel Lonceng Cinta di Sekolah Guru by Khairul Jasmi. The data of this research are quotation or the words were written by object that will have been observed, which going to individual social conflict with his self, family, and social environment. The source of this research is Lonceng Cinta di Sekolah Guru, the novel by Khairul Jasmi. There are ways for taking the data, those are : (1) reading and understanding the novel that wanted to observed, (2) marking all the event that topic going to the problems research, and (3) make a data list based on data list format. The invention of this research are individual social conflict in the novel Lonceng Cinta di Sekolah Guru by Khairul Jasmi involves the individual social conflict that with his self , with his family, and with social environment.